Problematika Surat Edaran Mahkamah Agung Nomor 2 Tahun 2023 Tentang Pelarangan Pencatatan Nikah Beda Agama Dalam Perspektif Hak Asasi Manusia - Habiburrahman, Muhammad; Maskur, Moh.; Shalihah, Aini (Sosio Yustisia: Jurnal Hukum dan Perubahan Sosial, 2023)
The Supreme Court of the Republic of Indonesia issued a Supreme Court Circular Letter (SEMA) Number 2 of 2023 concerning the Prohibition of Registration of Interfaith Marriages. However, the rules reap the pros and cons. Various international agreements on civil, political, economic, social and cultural rights as well as conventions on the elimination of discrimination against women have given men and women the right and freedom to marry without any religious restrictions. The purpose of this writing will be to answer the formulation of the problem, namely to find out the complexity of recording interfaith marriages from a human rights perspective with material for analysis of the Supreme Court Circular Letter Number 2 of 2023. The research method in this paper uses normative law with a statutory and conceptual approach. The results of the research show that there is SEMA No. 2 of 2023 guided by the Marriage Law No. 1 of 1974 (Marriage Law) which has a standard that regulates the complete rejection of the legality of marriage for all religions and beliefs. Even though these various international conventions are contradictory, it needs to be understood that Indonesia has rules regarding marriage which are contained in Law Number 1 of 1974 which should be the main legal rule (lex specialist) in its implementation. Meanwhile, the rules or norms contained in international conventions conflict with Law Number 1 of 1974. Therefore there is no legal problem with the existence of Law No. 1 of 1974 is different from the Universal Declaration of Human Rights as a fundamental instrument of human rights.